Structural Change of Gross Regional Product in the Subjects of Ural Federal District - Gamukin, Valeriy Vladimirovich (Economy of Regions, 2017)
The important factor of the stability of the national economy is the adaptive capability of regional economies to damping of external and internal factors of risk. It occurs thanks to the variety of the developed industry structures of the economy in regions as well as to the constant process of their transformation that finds reflection in the structure of the gross regional product (GRP). It is possible to consider three main strategies of the development of the structure of regional economy: 1 the reduction of the economies of regions to the balanced condition; 2 the emphasis on the individualization of the structure of regional economy; 3 the combined strategy, when regions with various structure of economy are integrated into macro-regions in which there is a compilation of structure. In the latter case, this can result in both the leveling of the GRP structure of the territorial subjects of the Russian Federation included in the region and its convergence to macro-region indicators, in general (for example, to the federal district’s indicators). For the confirmation of this hypothesis, the analysis of GRP of the subjects included in the Ural Federal District for the period of2005-2014 is carried out. As a result, a number of conclusions are formulated. Thus, the measurements with the use of the Ryabtsev Index and Szalai Index have shown that the GRP structure of autonomous areas is most close to the GRP structure of the federal district. At the same time, during the analyzed period, there was a reducing in a share of mining operations along with the increase in a share of GRP types referred to the auxiliary and social component of economic activity. In the federal district, there is a slow movement to a more balanced participation of regions of the district in the generation of GRP total amount. When using the authors index of the structure determined by the double calculation of the sum of squared deviations, the tendency towards the leveling of the GRP structure of the federal district, in general, is revealed. The results of the research can be applied when carrying out different types of the analysis of dynamics and structure of socio-economic indexes.